(untitled) - Shepherd, William G. (Englewood Cliffs, 1985)
This book introduce about basic concepts, market structure, performance, determinants, behavior and other variations, policies.
Keywords: Tổ chức công nghiệp (Lý thuyết kinh tế),Industrial organization (Economic theory)